Converter Ac-to-Ac With Additional Free- Wheeling Switches for Improving Power Factor and Reducing Harmonic Distortion - Mochamad Ashari1 (IPTEK The Journal for Technology and Science, 2008)
This paper presents development of single phase AC-to-AC converter with additional free-wheeling switches for improving the power factor and reducing harmonic distortion. The proposed system uses 2 switching types: the main switch and additional switch. The main switch is for controling the amplitude of the output voltage, while the additional switch is for releasing energy from inductive loads (free-wheeling switch). The main swicth is controlled by pulse width modulation (PWM), and the additional switch is modulated using the line frequency, 50 Hz. An AC-to-AC converter was simulated and built for laboratory test purposes. A conventional system, using thyristor and called Phase Control, was simulated for the system comparison. Results from simulation and laboratory tests show that the proposed system works properly. Using the same loads, the conventional system presents power factor as 0,34–0,71 and the voltage THD as 62.1%. The proposed system provides an improved power factor at nearly unity, and presents the total harmonic distortion of the voltage as 2.45%.